Diagnosing ANCA-associated vasculitis in ANCA positive patients: A retrospective analysis on the role of clinical symptoms and the ANCA titre. Issue 40 (October 2016) - Houben, Eline; Bax, Willem A.; van Dam, Bastiaan; Slieker, Walentina A.T.; Verhave, Gideon; Frerichs, Fenneke C.P.; van Eijk, Izhar C.; Boersma, Wim G.; de Kuyper, Guido T.M.; Penne, Erik L.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Currently no validated diagnostic system for antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is available. Therefore, diagnosing AAV is often challenging. We aimed to identify factors that lead to a clinical diagnosis AAV in ANCA positive patients in a teaching hospital in The Netherlands. In this study, all patients that tested positive for ANCA proteinase 3 (PR3) and/or myeloperoxidase (MPO) between 2005 and 2015 were analysed. Patients with a clinical diagnosis of AAV were compared with patients without a clinical diagnosis of AAV. Clinical symptoms and laboratory variables at presentation, including the ANCA titre, were collected for both patients with and without AAV. Clinical and laboratory variables related with AAV were investigated, using multivariable logistic regression. Two hundred thirty seven consecutive patients with a positive ANCA were included, of whom 119 were clinically diagnosed with AAV. Of the 118 ANCA positive patients without AAV, 87 patients had an alternative diagnosis, including inflammatory bowel disease (n = 24), other rheumatic diseases (n = 23), infection (n = 11), malignancy (n = 4), and other diagnoses (n = 25). In a multivariable regression model, a high ANCA titre (odds ratio [OR] 14.16, 95% confidence interval [CI] 6.93–28.94) and a high number of affected organ systems (OR 7.67, 95% CI 3.69–15.94) were associated with AAV. MPO and PR3 ANCA can be positive in a variety of diseases that mimic AAV. A higher ANCA titre and multiple affected organ systems may help to discriminate between AAV and other systemic illnesses in anti-PR3 and anti-MPO positive patients. A diagnostic scoring system incorporating these factors should be considered.